Sustainable agri-food investments require multi-sector co-development of decision tools. (March 2020) - Negra, Christine; Remans, Roseline; Attwood, Simon; Jones, Sarah; Werneck, Fred; Smith, Allison
Highlights: Science-based decision tools are required to catalyze investment in sustainable food systems. Agri-sector companies and investors need indices and other benchmarking mechanisms to inform decision making. Multi-sector tool co-development can increase utility in real-world applications. Limited research funding inhibits integration of science into investment decisions. Abstract: Global targets, such as the UN Sustainable Development Goals, and private sector commitments, such as deforestation-free supply chains, are stimulating growing demand for sustainable investment opportunities in the food and agriculture sector. Yet, the supply of such opportunities has been slow to materialize despite a proliferation of impact funds and other sustainability-focused funders seeking to direct global capital flows into the sector. This can be explained, in part, by the heterogeneous, multi-layered, and fragmented nature of agricultural production systems and food value chains and the poorly developed knowledge systems available to inform new types of investment. The volume of sustainability-oriented investment in the food and agriculture sector is likely to be hampered by the absence of a robust scientific evidence base and well-designed tools (e.g. indices and other benchmarking mechanisms) for harnessing knowledge to investment decision processes. At present, indicator-based tools for incorporating sustainability into agricultural value chains are being developed without adequate engagement by scientists. Collaborative co-development of decision tools by researchers and corporate and financial actors, that draws upon their distinct needs and knowledge sets, can improve the utility of these tools for real-world application (e.g. assessing non-financial returns; mitigating reputational risk). This paper proposes new requirements and strategies for the scientific community to contribute to co-development of science-based indicators and other decision tools that better enable agri-sector companies and investors to integrate food system sustainability considerations into management and capital allocation. It will present early lessons from multi-sector engagement in construction of indices, such as the Agrobiodiversity Index (ABDI), and review new modes for research institutions to engage with private sector partners.